Upaya Peningkatan Pengetahuan Pelaksanaan Discharge Planning di Ruang Bedah Rumah Sakit Umum Daerah Pringsewu - Retno Rahayu Ningsih; Rizki Yeni Wulandari; Yunina Elasari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
The sub-optimal execution of discharge planning often leads to an increase in readmission rates, ultimately resulting in patients bearing the costs of extended hospital stays. Data regarding the implementation of discharge planning in Indonesia reveals that 61% of nurses in Yogyakarta and 54% of nurses in Bandung do not conduct discharge planning Observational data indicated that nurses were not implementing discharge planning in accordance with the established Standard Operating Procedures (SOP) in the ward. The objective of this study is to evaluate the level of optimization in discharge planning practices at General Hospital of Pringsewu. Data collection methods conducted on November 9th 2024, involved interviews, questionnaires, and observations. The findings highlighted a nursing management issue that the sub-optimal implementation of discharge planning in the Surgical Ward at The General Hospital of Pringsewu. The planned intervention is to provide education on the importance of optimal discharge planning. The intervention was carried out on December 20th 2024, through educational sessions that emphasized the significance of discharge planning. Following the educational activity, there was a measurable improvement in the nurses' knowledge regarding discharge planning. Pre-test results ranged from 50% to 70%, while post-test results ranged from 80% to 95%. It is anticipated that the enhancement of nurses' knowledge will lead to the optimization of discharge planning practices in the surgical ward, thereby improving the overall quality of patient care provided by nurses.